1983
DOI: 10.1055/s-2007-1021964
|View full text |Cite
|
Sign up to set email alerts
|

Local Hemostasis with Fibrin Glue after Intracardiac Repair of Tetralogy of Fallot and Transposition of the Great Arteries

Abstract: In the last year fibrin glue Tissucol was used for local hemostasis in 21 patients subjected to correction of tetralogy of Fallot (ToF) and in 10 patients subjected to Senning-procedure in transposition of the great arteries (TGA). The postoperative blood loss was compared with the blood loss of 20 ToF-patients and 10 TGA-patients who had undergone correction one year ago without fibrin glue. Between the 2 groups were no differences in age, sex, bodyweight (BW), coagulation state or operative management. Two h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

1984
1984
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…The authors compared postoperative blood loss to 20 ToF patients and 10 TGA patients who had a correction one year ago without fibrin glue and found that two hours after surgery, bleeding with fibrin glue was lower than without fibrin glue ( p < 0.01) in patients with ToF and TGA. Over the next 18 h, the secretion of thoracic drains was identical in both groups [23]. This result could be considered similar to our result since the overall bleeding volume is similar in both groups.…”
Section: Discussionsupporting
confidence: 88%
“…The authors compared postoperative blood loss to 20 ToF patients and 10 TGA patients who had a correction one year ago without fibrin glue and found that two hours after surgery, bleeding with fibrin glue was lower than without fibrin glue ( p < 0.01) in patients with ToF and TGA. Over the next 18 h, the secretion of thoracic drains was identical in both groups [23]. This result could be considered similar to our result since the overall bleeding volume is similar in both groups.…”
Section: Discussionsupporting
confidence: 88%
“…TISSEEL has also been shown to be effective in repairing multiple VSDs in children, with good short‐ and long‐term results . Other reports describing TISSEEL use in major cardiac surgery include retrospective controlled studies that supported the ability of TISSEEL to reduce blood loss (assessed using chest tube outputs) during open‐heart surgery in adult and pediatric patients …”
Section: Resultsmentioning
confidence: 99%
“…They have shown beneficial results with respect to significantly shorter times to hemostasis than other commonly used agents/techniques in a variety of complex clinical situations 1,[6][7][8][11][12][13][14][15][16][17][18] and with respect to significant decreases in mortality and morbidity in spleen and liver injuries. 19 Our prospective controlled study evaluated the efficacy and safety of a fibrin sealant containing 500 IU/mL thrombin and synthetic aprotinin (referred to herein as FS) for the treatment of anastomotic suture-hole bleeding that is not amenable to additional sutures during placement of ePTFE vascular grafts.…”
mentioning
confidence: 99%